Influência do desbalanceamento da onda retangular na liga de alumínio 6063-T6 soldada pelo processo TIG-CA - Catarino, Jonny Max [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The weldability of the aluminum alloys is highly influenced by the weld current nature; it could interfere significantly on the desirable quality. The use of alternated current on the TiG welding processes, promote innumerous possibilities like, flexibilities on the change the wave frequency, positive current amplitude as the negative current amplitude, furthermore the actuations time of positive and negative polarity of electrode in the same wave cycle. The selected configuration has the important effect on the final properties on the weld bead. The use of alternated current on the aluminum alloys welding are largely used and has the finally, to promote the superficial oxide layer cleaning Al2O3, in the same time that it promote the weld penetration. On the literature is very common to find the affirmatives where the oxide layer cleaning of Al2O3 on the welding is linked on the positive time on the wave cycle, and the penetration is linked at the negative time for the same wave cycle. For this proposal research was realized the TIG-CA welding on the AA 6063-T6 aluminum alloys, by a bead-on-plate with the square wave, induced by weld current variations as the acting time of positive polarity of the electrode on the wave cycle. The weld current applied were 100 A, 120 A and 140 A. The initial conditions utilized was a balanced on 50% of acting time of positive polarity in the wave period in a 20 ms, followed by a unbalance of 32,5% and 15% of the actuation time of positive polarity in the electrode, keeping the unaltered frequency on 50 Hz for all configurations. Was observed that the unbalanced wave interfere direct on the final result of weld bead. The results for the selected configurations shows that decreasing the actuations time of electrode positive polarity on the wave cycle promote the reducations of death and wide on the weld bead. The obtained micrographia for a different actuations time of positive polarity shows that the...

A soldabilidade das ligas de alumínio é altamente influenciada pela natureza de correntes de soldagem, podendo esta interferir significativamente na qualidade a ser alcançada. O uso da corrente alternada em onda retangular no processo de soldagem TIG, permite inúmeras possibilidades tais como, flexibilidadeem alterar a frequencia da onda, amplitude da corrente positiva bem com o negativa, além dos tenpos de atuação da polaridade positiva e negativa do eletrodo para o mesmo ciclo de onda. A configuração selecionada tem efeito determinante no perfil e na propriedade final do cordão de solda. O uso da corrente alternada na soldagem das ligas de alumínio é amplamente utilizado e tem como finalidade, promover a limpeza da camada superficial do óxido Al2O3, enquanto promove a penetração da junta. Na literatura é comum encontrar afirmações que limpeza da camada de Al2O3 na soldagem está ligada ao tempo positivo do ciclo de onda, e a penetração está ligada ao tempo negativo do ciclo de onda. Para a pequisa proposta realizou-se a soldagem TIG-CA da liga de alumínio AA 6063-T6, por simples deposição sobre chapa com onda retangular, impondo-se variações tanto na corrente de soldagem como no tempo de atuação da polaridade positiva do eletrodo no ciclo na onda. As correntes de soldagem utilizadas foram 100 A, 120 A e 140 A. A condição inicial em termos de balanceamento foi de 50% do tempo de atuação da polaridade positiva em um período de onda de 20 ms, seguido do desbalanceamento para 32,5% e 15% de tempo de atuação da polaridade positiva do eletrodo, mantendo a frequência constante em 50 Hz para todas as configurações. Foi observado que o desbalanceamento de onda interfere diretamente no resultado final dos cordões de solda. Os resultados para as configurações selecionadas mostram que a diminuição do tempo de atuação da polaridade positiva do eletrodo no ciclo de onda promove redução de penetração e da...
Influence of unbalance of square wave on 6063-T6 aluminum alloys welded by AC-GTAW
Keywords: Soldagem; Aluminio; Ligas de aluminio; Welding